Geotechnical Characterization of Phosphate Mining Waste Materials for Use in Pavement Construction - Malaoui, Rachida; Harkati, El Haddi; Soltani, Mohamed Redha; Djellali, Adel; Soukeur, Abderraouf; Kechiched, Rabah (Engineering, Technology & Applied Science Research, 2023)
Waste rock materials are becoming widely used in road pavement and building constructions in many countries. In this work, experimental laboratory tests were carried out on the waste rock produced from the extraction of the phosphate in the Kef-Essenoun mine, to study the performance of road pavement foundations built with these types of material. Two types of waste, namely phosphatic limestone (type 1) and limestone (type 2), were initially tested to determine the most suitable one to be used in pavement structures. The characterization tests showed that the presence of carbonate-fluorapatite and carbonate-fluorapatite, and calcite, dolomite, and quartz are predominant in phosphatic limestone and limestone, respectively. The Los Angeles Abrasion (LA) and Micro-Deval (MD) values range from 59.9% to 90.4% and 42.05% to 86.31% for phosphatic limestone and from 43.64% to 95.88% and 38.25% to 75% for limestone. The CBR values of type 1 and type 2 waste were found to be 10.5% and 18.7% respectively. The results show that these materials, classified as B42ts and B42s respectively, could be used cautiously in capping layers and pavement backfilling materials. Furthermore, they must be treated with a hydraulic binder such as cement in order to improve their physical and mechanical properties.